Creation of Early Flowering Germplasm of Soybean by CRISPR/Cas9 Technology - Han, Jianan; Guo, Bingfu; Guo, Yong; Zhang, Bo; Wang, Xiaobo; Qiu, Li-Juan (Frontiers in Plant Science, 2019)
Soybean is an important economic crop and a typical short-day crop, sensitive to photoperiod, and has narrow geographical adaptative region, which limit the creation of transgenic materials and reduce the breeding efficiency of new varieties. In addition, the genetic transformation efficiency of soybean is lower than that of many other crops, and the available receptor genotypes are limited. In this study, CRISPR/Cas9 system and Agrobacterium-mediated transformation were used to introduce the CRISPR/Cas9 expression vector into soybean cultivator Jack and generated targeted mutants of E1 gene controlling soybean flowering. We obtained two novel types of mutations, 11 bp and 40 bp deletion at E1 coding region, respectively, and frameshift mutation that produced premature translation termination codons and truncated E1 protein, causing obvious early flowering under long-day condition. In addition, we didn’t observe any off-target effect by predicting and analyzing the potential off-target sites of E1 targets. Gene expression analyses of two novel mutants showed that the truncated E1 protein disinhibited GmFT2a/5a and increasing GmFT2a/5a gene expressions resulted in the obvious early flowering. We also obtained homozygous trans-clean mutants without T-DNA elements showing early flowering in long-day conditions. The photo-insensitive soybean transformation receptor we created laid a foundation for superior breeding excellent transgenic receptors suitable for high latitudes.